LEADERSHIP CHALLENGES IN DEVELOPING COUNTRIES: A CASE STUDY OF PAKISTANI HIGHER SECONDARY SCHOOLS - Ayaz, Maria (Transpublika Publisher, 2024)
The main objective of the research was to explore public school principals’ leadership problems and the techniques they used to overcome those problems. A qualitative research case study was conducted involving 10 public school principals (5 male and 5 female) from district Mardan of Pakistan. The data were gathered through semi-structured interviews and analyzed using the thematic analysis process. The results show that public school principals in Pakistan face multiple problems, including lack of authority, insufficient assistance from higher authorities, lack of resources, and teacher recruitment and retention issues. Additionally, the research also found that public school principals in Pakistan combat their problems with a variety of techniques, including creating a friendly rapport with teachers, engaging the community in the educational process, seeking help from higher authorities, and effectively leveraging resources. Moreover, this research has also examined Pakistani female public school principals’ problems and tactics. The results show that female public-school principals in Pakistan experience typical male principals’ problems, including lack of autonomy, insufficient resources, and support from higher authorities, as well as gender inequity. The results of the study have significant implications for policy and practice as the results of the study can inform specific policies and practices that can help in enlightening public schools’ leadership in Pakistan to improve the quality of education for students.